A method for developing organisation-wide manual handling based physical employment standards in a military context. Issue 11 (November 2018) - Carstairs, Greg L.; Ham, Daniel J.; Savage, Robert J.; Best, Stuart A.; Beck, Ben; Billing, Daniel C.
Abstract: The benefit of job-related employment standards in physically demanding occupations are well known. A number of methodological frameworks have been established to guide the development of physical employment standards for single job functions. In the case of an organisation comprised of multiple and diverse employment specialisations, such as the Australian Army, it is impractical to develop unique employment standards for each occupation. Objectives: To present an approach to organisational level physical employment standards development that seeks to retain occupationally specific task characteristics by applying a movement cluster approach. Design: Structured methodological overview. Methods: An outline of the research process used in performing job tasks analysis are presented, including the identification, quantification and characterisation, and verification of physically demanding manual handling tasks. The methodology used to filter task information collected from this job analyses to group manual handling tasks with similar characteristics (termed clusters), across a range of employment specialisations is given. Finally, we provide examples of test development based on these key manual handling clusters to develop a limited suite of tests with high content, criterion and face validity that may be implementable across a large organisation. Results: Job task analysis was performed on 57 employment specialisations, identifying 458 tasks that were grouped into 10 movement based clusters. The rationalisation of criterion tasks through clustering informed the development of a limited suite of tests with high content, criterion and face validity that may be implementable across a large organisation. Conclusion: This approach could be applied when developing physical employment standards across other multi-occupation organisations.